Research on solving the equilibrium point of 5DOF vehicle dynamics system based on homotopy method - Shuming Shi; Boshi Zhang; Zehui Ma; Qingchen Cheng; Guanghui Chen; Nan Lin (Scientific Reports)
Abstract The vehicle dynamic equilibrium point is an important content in the analysis of vehicle handling stability. However, due to the strong nonlinearity of the vehicle dynamics system and the coupling between different degrees of freedom, the analytical method cannot solve the equilibrium point of the system. When optimization method is used to solve the problem, it is often necessary to select the initial value and optimization parameters according to experience, and there is no general selection standard. In order to quickly and accurately solve the equilibrium point of 5DOF vehicle dynamics, this paper proposes a method for solving the equilibrium point of 5DOF vehicle dynamics based on the homotopy characteristics of the vehicle dynamics system, and compares the solution results and efficiency of the method with those of genetic algorithm and quasi-Newton algorithm. The results show that the homotopy method can make full use of the precise numerical solution of the equilibrium point of the 2DOF vehicle model, and realize the optimal solution of the equilibrium point of the 5DOF vehicle dynamics model, and can achieve both computational accuracy and computational efficiency.